High‐Energy‐Density Li‐Ion Batteries Employing Gradient Porosity LiFePO4 Electrode for Enhancing Li‐Ion Kinetics and Electron Transfer - Seungmin Han; Hyungjun Lee; Subi Yang; Jaeik Kim; Jinwoo Jeong; Yeseung Lee; Jinyoung Chun; Kwang Chul Roh; Patrick Joohyun Kim; Dongsoo Lee; Seho Sun; Woojin Jeong; et al. (Small Structures)
Lithium iron phosphate (LFP) cathodes are promising materials for energy storage device applications due to their thermal stability, chemical robustness, cost‐effectiveness, and long lifespan. However, their low electronic and ionic conductivity, as well as challenges in achieving high packing density in thick electrodes, limit their practical implementation. In this study, a gradient porosity LFP electrode with a high areal capacity of 6.3 mAh cm−2 and an electrode density of 2.5 g cc−1 is proposed. In electrodes with gradient porosity, binder migration is mitigated, ensuring a uniform binder distribution that enhances Li‐ion kinetics and adhesion strength between the electrode and aluminum current collector. Furthermore, by employing a particle with short charge carrier pathways in the bottom layer and a particle with a high tap density in the top layer, facile Li‐ion and electron transfer and easier electrode processing can be achieved. The resulting gradient porosity electrode with a high areal capacity of 6.3 mAh cm−2 exhibits excellent cycle stability over 100 cycles in full‐cell operation. These findings provide valuable insight into scalable strategies for high‐energy‐density, cost‐effective LFP‐based Li‐ion batteries.